Enhancement of calcium concentration in Zantedeschia plants : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Horticultural Science in Plant Science at Massey University - Rodil, Carlos N (Massey University, 1995)
As part of a research programme developing the use of enhanced calcium (Ca) concentrator of plant tissue as a means of control of bacterial soft rot in hybrid Zantedeschia, changes in Ca concentration were monitored using two methods of application. Gypsum application at 9 kg/m³ and a pre-plant vacuum application of 75% calcium chloride (CaCl₂) solution were used to follow changes in calcium (Ca) in concentration and its forms in tuber peel and matured leaves of hybrid Zantedescia plants. Throughout the period of growth, gypsum application increased approximately 2.0 mg/g Ca concentration of tuber peel tissue and matured leaves. The concentration in tuber peel tissue was increased to a maximum of 17.42 mg/g at 84 days after planting, then, declined to the concentration recorded at planting by 140 days. In contrast, the calcium concentration of the matured leaves increased continuously throughout the growing period. Plant available Ca in the gypsum amended medium was approximately three fold greater compared to that of the control (13.08 and 4.33mg/g at 14 days after planting or 15.53 and 4.96 mg/g at 98 days after palnting), and neither treatment showed any consistent trend of change over time. The decline in Ca concentration in tuber peel tissue coincided with the period of rapid tuber growth. Hence, it was suggested that this increase in tuber growth may have diluted the Ca concentration throughout the period of tuber enlargement. As evident by the continued accumulation of Ca within leaves, a further factor contributing to the decline in Ca concentration of the tuber peel may have been the limited ability of plants to regulate Ca distribution between the high (leaves) and low (tubers) transpiring tissues. lt was concluded that the application of gypsum is able to enhance the Ca concentration of the plant tissue. It was also concluded that there were no relationship between the trend of plant tissue calcium concentration and the plant available Ca in the growing medium. Pre-plant vacuum infiltration of 7.5% CaCl₂ increased the total Ca concentration of the tuber peel in addition to the different forms of Ca (i.e., soluble Ca, calcium oxalate and the Ca bound in the cell wall). However the increase was not maintained for the whole duration of growth. The concentration of all forms of Ca was increased to a maximum at post vacuum (PV) sampling and then subsequently declined before planting (BP). Once planted, and throughout the duration of growth, tubers vacuum infiltrated with 7.5% CaCl₂ did differences in the total Ca concentration or in the different forms of Ca were evident compared with those vacuum infiltrated with 0% CaCl₂ or the non vacuum treated tubers. Similarly with the matured leaves, the concentration of the total Ca and the different forms of Ca, did not result in any differences between treatments.
Keywords: Calla lilies; Effect of calcium; 300803 Horticultural crop improvement (incl. selection and breeding)